A Contribution to the Etiology of Diseases of Temporomandibular Joint - V. Machoň; V. Lukášová (Czech Dental Chamber, 2005)
The authors deal with the evaluation of etiological factors in the development of diseases of temporomandibular joint. The evaluated cohort consisted of 200 patients, 38 men and 162 women, the evaluated patients suffered from inflammatory degenerative diseases, intracapsular and extracapsular dysfunctions. Stress proved to be the most frequent etiological factor (in the inflammatory degenerative diseases in 52%, in intracapsular diseases in 40% and in extracapsular diseases in 27%), and the presence of vertebrogenic complaints (in the inflammatory degenerative diseases in 46%, in intracapsular diseases in 23% and in extracapsular diseases in 50%). Dentition dysfunctions proved to be another important factor.Results of the work should contribute to improved knowledge of the etiology in the origin of temporomandibular joint dysfunctions and consequently to higher efficiency of therapy.